PECULIARITIES OF ACCOUNTING AND ASSESSMENT OF BIOLOGICAL ASSETS IN ACCORDANCE OF IFRS 41 AGRICULTURE - Z.M. Shaukerova; К.К. Atabayeva; Janimkhan Indra (Academic Journal of Physical and Chemical Sciences, 2019)
International Financial Reporting Standard (IAS) 41 Has its own peculiarities of accounting and some difficulties in the assessment of biological assets. Agrarian enterprises are the basic economic resource potential for maintaining food security of the state. The development of market relations and the economy in the agricultural sector of the country predetermines the need to form an effective system of accounting and auditing the activities of agricultural organizations. Obtaining biological resources from uncontrolled sources, such as catching fish from the seas and oceans, harvesting wood by cutting down natural forests are not agricultural activities. The authors presented an example of assessing the changes resulting from biotransformation, such as the calculation of yield, average daily yield, protein / fat / carbohydrate content in the produced products, etc.